The Extracurricular Role of Hizbul Wathan in Shaping the Nationalist Character of Students at Ma Muhammadiyah 1 Medan - Hamdi, Ridho; Amin, Zulkifli (Indonesian Journal Education, 2024)
This research aims to determine the role of Hizbul Wathan extracurriculars in shaping the nationalist character of students at MA Muhammadiyah 1 Medan. This research was conducted using qualitative research methods. Data collection techniques are carried out through observation, interviews and documentation. This research was conducted at the Hizbul Wathan (HW) MA Muhammadiyah 1 Medan cohesive organization, the research subjects were the supervisors, administrators and members of HW. The findings in this study show that; 1) The HW scout leaders and members do not yet have a complete understanding of the concept of nationalism, but implicitly in running the organization the management and members have actually demonstrated the seeds of the spirit of nationalism in every planning and implementation of activities. 2) Strengthening the organization with a foundation of nationalist spirit based on state ideology and Muhammadiyah values. Through strong organizational commitment, the spirit of nationalism will flow within the HW scout members. 3) HW scout members will become nationalists. This was demonstrated in HW's scouting activities at MA Muhammadiyah 1 Medan through respecting the flag, avoiding the spread of fake news, and not being involved in negative activities. To encourage the development of national values ??and a sense of nationalism in students, HW coaches, Civics teachers, and Social Sciences teachers use varied methods supported by flag ceremonies, sports competitions, and local arts events.